2008
DOI: 10.7326/0003-4819-149-7-200810070-00004
|View full text |Cite
|
Sign up to set email alerts
|

Stool DNA and Occult Blood Testing for Screen Detection of Colorectal Neoplasia

Abstract: Background Stool DNA testing is a new approach to colorectal cancer detection. Few data are available from the screening setting. Objective To compare stool DNA and fecal blood testing for detection of screen-relevant neoplasia (curable-stage cancer, high-grade dysplasia, or adenomas >1 cm). Design Blinded, multicenter, cross-sectional study. Setting Communities surrounding 22 participating academic and regional health care systems in the United States. Participants 4482 average-risk adults. Measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
171
0
14

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(193 citation statements)
references
References 48 publications
8
171
0
14
Order By: Relevance
“…Since then, many studies have been devoted to vimentin methylation. Follow-up studies have obtained similar results and thus have reinforced the utility of vimentin as a standalone biomarker [47,54,55,59,61] . This has led to the commercialization of a single-gene stool kit for CRC detection based on vimentin methylation.…”
Section: Biomarkers Of Dna Methylation In Bloodmentioning
confidence: 68%
“…Since then, many studies have been devoted to vimentin methylation. Follow-up studies have obtained similar results and thus have reinforced the utility of vimentin as a standalone biomarker [47,54,55,59,61] . This has led to the commercialization of a single-gene stool kit for CRC detection based on vimentin methylation.…”
Section: Biomarkers Of Dna Methylation In Bloodmentioning
confidence: 68%
“…The studies that attempted to reduce verification bias are listed in Table 2. [51][52][53][54][55][56][57][58][59][60] These 10 studies included 185 subjects with colorectal cancer and 31,804 controls. Seven studies reduced verification bias by performing colonoscopy on all of the potential subjects 51,54-56,58-60 while 3 studies used longitudinal follow-up for at least 2 years.…”
Section: Included Studiesmentioning
confidence: 99%
“…9,[11][12][13][14][15][16][17][18] The reliability of DNA amplification shown by our QRTPCR assay indicates that DNA isolated from material obtained with the new collection technique is of much higher quality than widely used DNA extracted from stool.…”
Section: Early Detection and Diagnosismentioning
confidence: 92%
“…Purification of human DNA from stool is difficult, [14][15][16] and there is no unique molecular signature reliably indicating cancer presence. The latter difficulty resulted in the use of multimarker assays, 3,9,[11][12][13][14][15][16][17][18] making the cost-effectiveness of the approach a major issue. 9,[19][20][21] It has been suggested that exfoliated colonocytes collected directly from the surface of colonic mucosa could serve for diagnostic and research applications better than stool-derived material.…”
mentioning
confidence: 99%
See 1 more Smart Citation